Advanced quantitative analysis of epitaxial SiGe composition on production wafer for logic devices. (7th November 2017) - Penley, Christopher; Walker, Michael; Wilson, Michael; Billingsley, Daniel; Raviswaran, Arvind; Phillips, Shane
Abstract : Quantitative analyses of in situ boron‐doped SiGe composition on production wafers for 14 and 20‐nm logic devices were successfully characterized using advanced, small area Time‐of‐Flight Secondary Ion Mass Spectrometry analysis methods. The quantification of dopant levels in SiGe offered an improved method for tool‐to‐tool matching, process monitoring, and improvement, and performing this function accurately was necessary to enable advanced SiGe technology development that ensured world class manufacturing requirements were met. The boron concentration was measured with Time‐of‐Flight Secondary Ion Mass Spectrometry, based on a single Si1‐x Gex /Si on silicon substrate standard, which exhibited excellent matching with corresponding inline XRF intensity data. Time‐of‐Flight Secondary Ion Mass Spectrometry accurately characterized SiGe composition with adequate sensitivity to detect small boron concentration variations to fine‐tune process parameters. This provided insight to the relationship between overlap capacitance and Rodlin measurements with SiGe dopant levels and ultimately led to device performance improvement.